2019
DOI: 10.1073/pnas.1915141116
|View full text |Cite
|
Sign up to set email alerts
|

Aged hind-limb clasping experimental autoimmune encephalomyelitis models aspects of the neurodegenerative process seen in multiple sclerosis

Abstract: Experimental autoimmune encephalomyelitis (EAE) is the most common model of multiple sclerosis (MS). This model has been instrumental in understanding the events that lead to the initiation of central nervous system (CNS) autoimmunity. Though EAE has been an effective screening tool for identifying novel therapies for relapsing-remitting MS, it has proven to be less successful in identifying therapies for progressive forms of this disease. Though axon injury occurs in EAE, it is rapid and acute, making it diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 75 publications
(89 reference statements)
0
10
0
Order By: Relevance
“…The animals presented with reduced weight likely due to severe motor deficits resulting in reduced feeding ability (Cendelin, 2014). Hindlimb clasping is an indicator of lesions in the motor pathway in several mouse models of neurodegeneration (Lalonde & Strazielle, 2011;Cahill et al, 2019), including Elp2 and Elp6 mutant mice (Kojic et al, 2018(Kojic et al, , 2021, and was found to be prominent in the Elp6L118W animals as well (Fig 5B). A severe motor phenotype was consistently observed across different behavioral tests (Fig 5C).…”
Section: Modeling Elp6l118w In Mice Recapitulates Phenotypic Features...mentioning
confidence: 94%
“…The animals presented with reduced weight likely due to severe motor deficits resulting in reduced feeding ability (Cendelin, 2014). Hindlimb clasping is an indicator of lesions in the motor pathway in several mouse models of neurodegeneration (Lalonde & Strazielle, 2011;Cahill et al, 2019), including Elp2 and Elp6 mutant mice (Kojic et al, 2018(Kojic et al, , 2021, and was found to be prominent in the Elp6L118W animals as well (Fig 5B). A severe motor phenotype was consistently observed across different behavioral tests (Fig 5C).…”
Section: Modeling Elp6l118w In Mice Recapitulates Phenotypic Features...mentioning
confidence: 94%
“…14,39 We therefore proceeded to test the ability of isoDGR-specific immunotherapy to preserve motor and cognitive function in Pcmt1 -/- mice using clasping and ledge behaviour tests. 4042 Six-week-old PCMT1 +/+ and Pcmt1 +/- mice displayed normal extension reflex in the hind-limbs and used body torsion when suspended in the air. In contrast, Pcmt1 -/- mice exhibited severe hind-limb clasping and high dysfunction scores than were improved upon treatment with isoDGR-specific mAb (Fig.1F).…”
Section: Resultsmentioning
confidence: 99%
“…Hindlimb clasping is a neurologic sign often found in transgenic or experimental mouse models of neurodegenerative diseases. It is associated with lesions or abnormalities in different areas of the spinal cord or the brain, and commonly due either to myelin defects or to axonal degeneration (Adebola et al, 2015; Cahill et al, 2019; De Pace et al, 2018; Scherz et al, 2018). In our study, it is unlikely that the behavior is due to axonal degeneration, as we could not observe signs of increased axonal damage or of axonal shrinkage.…”
Section: Discussionmentioning
confidence: 99%